Cardiac fibrogenesis: an immuno-metabolic perspective - Hoque, Md Monirul; Gbadegoye, Joy Olaoluwa; Hassan, Fasilat Oluwakemi; Raafat, Amr; Lebeche, Djamel (Frontiers in Physiology, 2024)
Cardiac fibrosis is a major and complex pathophysiological process that ultimately culminates in cardiac dysfunction and heart failure. This phenomenon includes not only the replacement of the damaged tissue by fibrotic scar produced by activated fibroblasts/myofibroblasts, but also a spatiotemporal alteration of the structural, biochemical, and biomechanical parameters in the ventricular wall eliciting a reactive remodeling process. Though mechanical stress, post-infarct homeostatic imbalances, and neurohormonal activation are classically attributed to cardiac fibrosis, emerging evidence supports the roles of immune system modulation, and metabolic dysregulation in the initiation and progression of cardiac fibrogenesis.Adaptive changes, immune cell phenoconversions, and metabolic rewiring in the cardiac nonmyocyte population provide an initial protection but persistent altered metabolic demand eventually contributes to adverse remodeling of the heart. Altered energy metabolism, mitochondrial dysfunction, various immune cells, immune mediators, and cross-talks between the immune cells and cardiomyocytes play crucial roles in orchestrating the transdifferentiation of fibroblasts and ensuing extracellular matrix remodeling of the heart. Manipulation of the metabolic plasticity, fibroblast-myofibroblast transition, and modulation of immune response may hold promise for favorably modulating the fibrotic response. Although the immunologic and metabolic perspectives of fibrosis in the heart are reported in the literature, they lack a comprehensive sketch bridging these two arenas and illustrating the synchrony between them. This review aims to provide a comprehensive overview of the intricate relationship between different cardiac immune cells and metabolic pathways as well as summarize the current understanding of the involvement of immunemetabolic pathways in cardiac fibrosis and attempts to identify some of the previously unaddressed questions that require further investigations. Moreover, the potential therapeutic strategies and emerging pharmacological interventions, including immune and metabolic modulators, that show promise in preventing or attenuating cardiac fibrosis and restoring cardiac function will be discussed.